Cholera in Azov area - O. N. Domashenko; T. A. Belomerya; N. V. Martynova; G. N. Daragan; O. O. Demkovich; U. V. Malakhova; G. I. Zemlyanskaya; D. M. Popova (Журнал инфектологии, 2015)
The purpose of research is analysis of clinical course and treatment results of patients with cholera in the Azov area. Materials and methods. During the period from 29.05.2011 to 19.08.2011 33 cases of cholera (32 adults and 1 child) and 25 vibrio carriers (22 adults and 3 children), which were caused by toxigenic strains of Vibrio cholera El Tor serogroup O1 Ogawa. Results. Likely factors of disease transmission in Mariupol are sea and river water, and the fish that were caught in the waters of the city. Typical and watery diarrhoea, vomiting, abdominal pain and lack of normal body temperature, dehydration syndrome, characterized clinical cholera for adults in most cases. The mean duration of diarrhoea was 6,6 days. At 46.9% observed atypical symptoms in 10 (31,3%) – abdominal pain (1 patient cramping in 7 cases, localized in the epigastria region, at 2-over stomach). In 5 patients (15,6%) had an increase in body temperature to 37,2–37,7 degrees Celsius. In 15 (46,9%) patients had severe nausea accompanied by vomiting. Easy for cholera was observed in 1 (3.1%), moderate – in 14 (43,8%), heavy – in 17 (53,1%) patients. Dehydration I level is set at 4 (12,5%), II – from 6 (18,7%), III – in 18 (56,3%), IV – 4 (12,5%) patients. Cholera outbreak was characterized by a predominance of severe disease and severe dehydration (III and IV), which was observed in 68.8% of patients. The decisive factor in the treatment of cholera patients was initiated in a timely manner rehydration therapy, in particular the introduction of the solution «Trisol». Against the background of rehydration therapy hyperkalaemia was observed in 9,4% of cases, vascular rehydration at 9,4%, the cell rehydration in 3,1% of patients. Fatal accidents cholera outbreaks have not been observed. Conclusion. Clinical diagnosis of cholera and the provision of medical care in the prehospital phase were poor, indicating the need for systematic conducting training seminars among experts of ambulance, as well as doctors of primary medical network. Cholera hospitals (or base hospitals) must be equipped with a mobile diagnostics (ultrasound, X-rays) and modern laboratory equipment. The required list of drug supply cholera hospitals should be expanded in view of possible complications and comorbidities.